Extramedullary disease in Waldenström macroglobulinemia: A population‐based observational study - Simon Østergaard; Lars Munksgaard; Torsten Holm Nielsen; Troels Hammer; Lars Møller Pedersen; Mette Ølgod Pedersen; Lise Mette Rahbek Gjerdrum (eJHaem, 2024)
Abstract Introduction: Extramedullary disease (EMD) is a rare manifestation of Waldenström macroglobulinemia (WM), and its clinical and prognostic implications are poorly understood. Methods: In this single‐center study, we investigated the clinical significance of EMD in a cohort of 469 WM patients. Results: EMD was identified in 30 (6.4%) patients, with the central nervous system, kidneys, and lungs being the most frequently affected sites. The cumulative incidence of EMD was 12.6% at 15 years. Median overall survival rates at 5 and 10 years for patients with EMD were 63% and 37%, respectively. Conclusion: Our findings indicate a persistent risk of EMD throughout the disease course, with no significant impact on long‐term survival.